The Role of Socioeconomic Marginalization in the Radicalization of Jihadi Foreign Fighters from Europe - Eylem Kanol (Studies in Conflict & Terrorism, 2023)
Is socioeconomic marginalization associated with the radicalization of European foreign fighters? I analyze biographical data on 1019 foreign fighters from France, Germany, and the United Kingdom and compare their level of education and unemployment rate with those of the population most at risk of radicalization, namely the young male Muslim population within the respective country. Overall, the results indicate that compared to the population at the highest risk of radicalization, foreign fighters do not appear to be disproportionately socioeconomically deprived. An analysis of survey data on support for foreign fighters conducted among the Muslim minority in Germany further underlines these findings.
Keywords: 300